2022
DOI: 10.1002/bit.28153
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of a thermophilic Argonaute from archaeon Thermococcus thioreducens

Abstract: Prokaryotic Argonaute proteins (pAgos) play an important role in host defense against invading genetic elements. The functional diversities make pAgos very promising in development of novel nucleic acid manipulation tools and attract increasing attentions. Here, we reported the in vitro characterization of an Argonaute protein from archaeon Thermococcus thioreducens (TtrAgo) and its example of application in hepatitis B virus DNA detection. The results showed that TtrAgo functions as a programmable DNA endonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
8
5
0
Order By: Relevance
“…In summary, similar to previously characterized pAgos from thermophilic prokaryotes such as TtAgo, PfAgo, MjAgo, and FpAgo (Swarts et al, 2014a;Swarts et al, 2015;Willkomm et al, 2017;Zander et al, 2017;Guo et al, 2021), TtdAgo prefers to use DNA guides to cleave DNA targets. This result is similar to a simultaneous study of TtrAgo (TtdAgo) reported earlier by Fang et al (2022). However, in contrast to most eAgos and pAgos including hAgo2, IbAgo, KmAgo, and MbpAgo (Rivas et al, 2005;Kropocheva et al, 2021;Li W. et al, 2022), whose target cleavage resulted in a shift of the cleavage site mediated by 5′-OH guides compared to that using 5′-P-gDNA as shown by Fang et al (2022), we did not observe the cleavage position shift for TtdAgo with 5′-P-gDNA compared to that with 5′-OH-gDNA.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In summary, similar to previously characterized pAgos from thermophilic prokaryotes such as TtAgo, PfAgo, MjAgo, and FpAgo (Swarts et al, 2014a;Swarts et al, 2015;Willkomm et al, 2017;Zander et al, 2017;Guo et al, 2021), TtdAgo prefers to use DNA guides to cleave DNA targets. This result is similar to a simultaneous study of TtrAgo (TtdAgo) reported earlier by Fang et al (2022). However, in contrast to most eAgos and pAgos including hAgo2, IbAgo, KmAgo, and MbpAgo (Rivas et al, 2005;Kropocheva et al, 2021;Li W. et al, 2022), whose target cleavage resulted in a shift of the cleavage site mediated by 5′-OH guides compared to that using 5′-P-gDNA as shown by Fang et al (2022), we did not observe the cleavage position shift for TtdAgo with 5′-P-gDNA compared to that with 5′-OH-gDNA.…”
Section: Resultssupporting
confidence: 92%
“…This result is similar to a simultaneous study of TtrAgo (TtdAgo) reported earlier by Fang et al (2022). However, in contrast to most eAgos and pAgos including hAgo2, IbAgo, KmAgo, and MbpAgo (Rivas et al, 2005;Kropocheva et al, 2021;Li W. et al, 2022), whose target cleavage resulted in a shift of the cleavage site mediated by 5′-OH guides compared to that using 5′-P-gDNA as shown by Fang et al (2022), we did not observe the cleavage position shift for TtdAgo with 5′-P-gDNA compared to that with 5′-OH-gDNA. This result may be due to the different targets and reaction conditions such as the concentration of divalent ion and the temperature both being different.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations